Credit Risk Management Efficiency and Sustainable Profitability in Commercial Banks of Kathmandu Valley - Basnyat, Neha; Kaur, Kamaljeet (Journal of Advanced Academic Research, 2026)
This paper analyses how the efficiency of credit risk management influences sustainable profitability of commercial banks in Kathmandu Valley, Nepal. The study is based on the risk-return trade-off framework; it specifically examines the potential significant impact of non-performing loans (NPL) and capital adequacy ratio (CAR) on the profitability of the banks in terms of their return on assets (ROA) and return on equity (ROE). The secondary data using a quantitative research design were collected using published annual reports of the selected commercial banks across five years (FY 2076/77 to 2080/81). To test the above hypotheses, Pearson correlation analysis, regression models, and ANOVA tests were used. The empirical findings demonstrate that NPL and ROE have a statistically significant negative correlation (r = -0.695, p = 0.026), whereas the correlation between NPL and ROA is moderate and negative. Further, NPL is found to explain 35.4% of the change in ROA (R2 = 0.354), which results in the acceptance of H1. Even though CAR has a positive correlation with profitability, the regression model is not significant (F = 2.917, p = 0.148), which leads to the rejection of H2. All in all, the results prove that the quality management of loans is more significant than the capital strength itself in terms of maintaining long-term profitability. The analysis offers evidence on a regional basis that has a significant implication to the management of banks and regulators in Nepal.